Effective Succession Planning Practices Pose Challenges within African Establishments (International Journal of Scientific Research and Management (IJSRM), 2023)
There has been a growing demand for equilibrium in the worldwide high dependency ratio. The overall increase in lifespan with a corresponding decrease in fertility rates has resulted in a populace that is predominantly composed of senior citizens. At times, institutions tend to prioritize their own organizational requirements above the needs and interests of their individual employees. Such an approach often results in the exclusion of employees and their willingness to transfer, assume new positions, or participate in developmental activities being overlooked. This can lead to demotivation among employees and ultimately impact the overall performance of the institution. Succession planning must have the full cooperation of all involved parties to succeed. If organizations want to be successful, particularly in realizing their vision-mission, it is important to find the right people who will be part of their journey toward greatness. Achieving success today requires both hard work and smart work, not just one or the other. In our interconnected world, organizations are no longer isolated entities. To ensure continuity, succession planning is a deliberate process that prepares employees for promotion within the organization. This tool helps management identify critical roles and individuals possessing the necessary skills. Typically, employees are hired based on their knowledge, rather than their ability to perform tasks. Passing on organizational knowledge to potential successors can significantly reduce the amount of time needed to adapt to a new position.